Suitability of corn flour in steamed bread matrices of corn‐wheat composite flour: a thermal, rheological and nutritional approach - Chen, Peixia; Hong, Jing; Liu, Chong; Zheng, Xueling; Tian, Xiaohui; Shang, Jiaying; Omer, Saeed Hamid Saeed (International journal of food science & technology, 2023)
This study investigated the thermal, rheological, morphological, and nutritional properties of corn‐wheat composite steamed bread (CWCSB) with different heat treatment methods (steaming, high temperature and high pressure, extrusion) and fermentation methods (yeast and sourdough). The results indicated that sourdough fermentation (SF) improved the textural properties and protein digestibility of CWCSB compared to yeast fermentation (YF). All heat treatments enhanced the elastic behaviour of the dough, with the extrusion method showing a higher G′ value. Both extrusion and steaming treatments resulted in reduced hardness, viscosity, and chewiness of the CWCSB. Due to the flash evaporation effect, a denser dough structure was formed by extrusion, thus reducing enzyme accessibility and resulting in an increased content of slowly digestible starch from 5.09% to 11.21%. In conclusion, extrusion combined with SF could be used as a potential method to improve the suitability of corn flour in steamed bread of corn‐wheat composite flour.